The Influence of Printing Parameter Variations on the Dimensional Accuracy of 3D Nylon Carbon FDM Prints Using the Grey-Taguchi Method - Gilang Argya Dyaksa; Felix Krisna Aji Nugraha; Heryoga Winarbawa; Kristian Ismartaya; Robertus Bellarmino Radya Ananda; Hadrianus Felin Saputra (Faculty of Science and Technology, Universitas Sanata Dharma, 2026)
The dimensional accuracy of the printed specimen in the process of forming a workpiece with carbon fiber material using the Creality K1 Max printer machine requires a combination of parameters in the printing process. The printing type using Fused Deposition Modeling (FDM) is a very popular type of printing process, in this process the filament of the raw material is heated to form the desired product. Nylon carbon was chosen because it has high strength and heat resistance, so it is quite potential for various types of applications. Dimensional accuracy is a major problem in the printing process using 3D printing, especially if the printed product will be assembled either in a mechanical system or a non-mechanical system. The results of the dimensional accuracy of the object printing process are greatly influenced by the selection of parameters used in the printing process. The printing parameter optimization process uses the Grey-Taguchi method, this method was chosen because this method combines multi-dimensional workpieces according to product quality. The specimen or workpiece uses the ASTM D638 standard. Dimensions are 165 length, 13 neck, 19 width, and 7 mm thick. Deviation or dimensional accuracy is based on the largest GRG value in the parameter composition. The research results obtained the following printing parameter factors: a layer thickness of 0.2 mm, a nozzle temperature of 280°C, and a printing speed of 60 mm/s, also layer thickness is the most influence parameter that increasing the dimensional accuracy.